tìm x
-12+3.(-x+7)=-18
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) x= 1/4
b) x= -7/144
c) x= 25/6
d) x=17/7
e) x= 80/63
f) x= -45/14
-12+3(-x+7)=-18
-9(-x+7)=-18
9x-63=-18
9x=-18+63=45
x=45:9=5
-12 + 3 . (-x + 7) = -18
→ 3 × (-x + 7) = -18 - (-12)
→ 3 × (-x + 7) = -18 + 12
→ 3 × (-x + 7) = -6
→ -x + 7 = -6 : 3
→ -x + 7 = -2
→ -x = -2 - 7
→ -x = -9
→ x = 9
Vậy x = 9
\(a,\Rightarrow\left[{}\begin{matrix}x=18\\x=-18\end{matrix}\right.\\ b,\Rightarrow\left[{}\begin{matrix}x=\dfrac{3}{5}\\x=-\dfrac{3}{5}\end{matrix}\right.\\ c,\Rightarrow x:\left(-\dfrac{1}{60}\right)=2\Rightarrow-60.x=2\Rightarrow x=-\dfrac{2}{60}=-\dfrac{1}{30}\)
a.
\(10-2\left(4-3x\right)=-4\)
\(\Leftrightarrow2\left(4-3x\right)=10+4\)
\(\Leftrightarrow2\left(4-3x\right)=14\)
\(\Leftrightarrow4-3x=7\)
\(\Leftrightarrow3x=-3\)
\(\Leftrightarrow x=-1\)
b.
\(-12+3\left(-x+7\right)=-18\)
\(\Leftrightarrow3\left(-x+7\right)=-18+12=-6\)
\(\Leftrightarrow-x+7=-6:3=-2\)
\(\Leftrightarrow x=9\)
c.
\(-45:5.\left(-3-2x\right)=3\)
\(\Leftrightarrow-9.\left(-3-2x\right)=3\)
\(\Leftrightarrow-3-2x=-\dfrac{1}{3}\)
\(\Leftrightarrow2x=-\dfrac{8}{3}\)
\(\Leftrightarrow x=-\dfrac{4}{3}\notin Z\left(loại\right)\)
Câu này em ghi sai đề?
d.
\(3x-28=x+36\)
\(\Leftrightarrow2x=28+36\)
\(\Leftrightarrow2x=64\)
\(\Leftrightarrow x=32\)
e.
\(\left(-12\right)^2.x=56+10.13x\)
\(\Leftrightarrow144x=56+130x\)
\(\Leftrightarrow144x-130x=56\)
\(\Leftrightarrow14x=56\)
\(\Leftrightarrow x=4\)
c: Ta có: \(\left|x+\dfrac{5}{6}\right|:\dfrac{4}{5}=\dfrac{3}{8}\)
\(\Leftrightarrow\left|x+\dfrac{5}{6}\right|=\dfrac{3}{8}\cdot\dfrac{4}{5}=\dfrac{3}{10}\)
\(\Leftrightarrow\left[{}\begin{matrix}x+\dfrac{5}{6}=\dfrac{3}{10}\\x+\dfrac{5}{6}=-\dfrac{3}{10}\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{-8}{15}\\x=-\dfrac{17}{15}\end{matrix}\right.\)
-12+3(-x+7)=-18
-12-3x+21=-18
9-3x=-18
3x=27
x=9
- 12 + 3 ( - x + 7 ) = - 18
- 3x + 3 . 7 = -18 + 12
- 3x + 21 = - 6
- 3 x = - 6 - 21
- 3x = - 27
x = - 27 : ( - 3 )
x = 9